2009
DOI: 10.1017/s1355617709090353
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive differences between pedophilic and nonpedophilic child molesters

Abstract: Although some evidence exists that child molesters may be characterized by structural and functional brain abnormalities, findings across studies are inconsistent. Past cognitive research in this area has been extensively criticized for relying on conceptually weak batteries, measures of questionable reliability, and poorly defined samples (i.e., failing to distinguish between pedophilic and nonpedophilic child molesters). The present study aimed to address the weaknesses of past research by comparing 40 child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
51
4
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 57 publications
11
51
4
1
Order By: Relevance
“…The notion that pedophilia is related to frontal dysfunction has moreover been challenged by studies in which pedophilic subjects displayed a slower processing speed but no increased error rate. These results would be in accordance with a more deliberate response style and greater self-monitoring [15,16], and they would better correspond to findings from clinical work showing that pedophilic subjects often abuse children repeatedly over a period of many years without arousing anybody's suspicion and that they often entangle their victims gradually into abuse. This behavioral pattern would rather indicate a deliberate than an impulsive modus operandi.…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…The notion that pedophilia is related to frontal dysfunction has moreover been challenged by studies in which pedophilic subjects displayed a slower processing speed but no increased error rate. These results would be in accordance with a more deliberate response style and greater self-monitoring [15,16], and they would better correspond to findings from clinical work showing that pedophilic subjects often abuse children repeatedly over a period of many years without arousing anybody's suspicion and that they often entangle their victims gradually into abuse. This behavioral pattern would rather indicate a deliberate than an impulsive modus operandi.…”
Section: Introductionsupporting
confidence: 77%
“…From other studies on executive functions in pedophilia we know that pedophilic subjects showed a slower processing speed in combination with similar error rates in executive tasks [15,16]. The authors of these studies concluded that pedophilic subjects display a more deliberate response pattern, which these authors related to stronger self-monitoring.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Again, while some of these studies suggest somewhat generalized dysfunction, reflected in lower overall IQ (Cantor, Blanchard, Robichaud, & Christensen, 2005), poorer academic functioning , and slower processing speed (Suchy, Whittaker, Strassberg, & Eastvold, 2009b), others suggest more focal cognitive problems. These latter studies Correspondence and reprint requests to: Angela Eastvold, PhD, James Haley Veteran's Administration, Mental Health & Behavioral Sciences, 116B, 13000 Bruce B. Downs Blvd., Tampa, FL 33612.…”
Section: Introductionmentioning
confidence: 99%